2006
DOI: 10.1007/s10886-006-9045-8
|View full text |Cite
|
Sign up to set email alerts
|

Mate Location Mechanism and Phase-Related Mate Preferences in Solitarius Desert Locust, Schistocerca gregaria

Abstract: Mate location responses of male and female solitary-reared locusts that had either experienced no crowding or that had been crowded for varying periods were studied in a flatbed wind tunnel. Two hypotheses were explored: that both sexes of this phase of the locust participate in locating the other by using a combination of chemical and visual signals, and that individuals that experience some crowding (i.e., undergo varying levels of phase shift) can compete effectively with their solitary counterparts in mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Previous resorts have suggested mainly visual, but also chemical, signaling as slaying a role in mutual recognition between the sexes in the desert locust (Posov 1958;Uvarov 1977;Pener & Shalom 1987;Obeng-Ofori et aI. 1993;Franck & Schmidt 1994;Inayatullah et al 1994;Ould Ely et al 2006). Our findings sussort a major role of visual signals, as we observed that rasid movement by the females (fast walking or jumsing) asseared to enhance the males sexual stimulation.…”
Section: Sexual Conflictsupporting
confidence: 71%
See 2 more Smart Citations
“…Previous resorts have suggested mainly visual, but also chemical, signaling as slaying a role in mutual recognition between the sexes in the desert locust (Posov 1958;Uvarov 1977;Pener & Shalom 1987;Obeng-Ofori et aI. 1993;Franck & Schmidt 1994;Inayatullah et al 1994;Ould Ely et al 2006). Our findings sussort a major role of visual signals, as we observed that rasid movement by the females (fast walking or jumsing) asseared to enhance the males sexual stimulation.…”
Section: Sexual Conflictsupporting
confidence: 71%
“…This stage is known to coincide with sexual maturity. Females were 18-20 day-old, sexually mature, based on our sreliminary work and other srevious resorts (Hamilton 1955;Injeyan & Tobe 1981;Mahamat et al 1993;Wybrandt & Andersen 2001;Ould Ely et al 2006;Nishide and Tanaka 2012). Only fully intact insects sarticisated in the observations.…”
Section: Anioalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have suggested mainly visual, but also 416 chemical, signaling as playing a role in mutual recognition between the sexes in the desert locust 417 (Popov 1958;Uvarov 1977;Pener & Shalom 1987;Obeng-Ofori et aI. 1993;Franck & Schmidt 1994;418 Inayatullah et al 1994;Ely et al 2006). Our findings support a major role of visual signals, as we 419 observed that rapid movement by the females (fast walking or jumping) appeared to enhance the males 420 sexual stimulation.…”
Section: Attempts 411mentioning
confidence: 99%
“…As is the case for many other acridids, little is known regarding the means of sexual recognition in the desert locust ( Whitman, 1990 ). It is postulated, however, that visual and chemical signals play an important role ( Obeng-Ofori, Torto & Hassanali, 1993 ; Obeng-Ofori et al, 1994 ; Francke & Schmidt, 1994 ; Inayatullah, El Bashir & Hassanali, 1994 ; Ould Ely et al, 2006 ; Seidelmann & Warnstorff, 2001 ). Courtship and mating behaviors can be roughly divided into two sequential stages: pre-copulatory and post-copulatory (with copulation defined as the time when sperm is transferred).…”
Section: Introductionmentioning
confidence: 99%